Fighting Post-COVID and ME/CFS – development of curative therapies - Scheibenbogen, Carmen; Bellmann-Strobl, Judith Theresia; Heindrich, Cornelia; Wittke, Kirsten; Stein, Elisa; Franke, Christiana; Prüss, Harald; Preßler, Hannah; Machule, Marie-Luise; Audebert, Heinrich; Finke, Carsten; Zimmermann, Hanna Gwendolyn; et al. (Frontiers in Medicine, 2023)
The sequela of COVID-19 include a broad spectrum of symptoms that fall under the umbrella term post-COVID-19 condition or syndrome (PCS). Immune dysregulation, autoimmunity, endothelial dysfunction, viral persistence, and viral reactivation have been identified as potential mechanisms. However, there is heterogeneity in expression of biomarkers, and it is unknown yet whether these distinguish different clinical subgroups of PCS. There is an overlap of symptoms and pathomechanisms of PCS with postinfectious myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). No curative therapies are available for neither ME/CFS nor PCS. The mechanisms identified so far provide targets for therapeutic interventions. To accelerate the development of therapies, we propose evaluating drugs targeting different mechanisms in clinical trial networks using harmonized diagnostic and outcome criteria and subgrouping patients based on a thorough clinical profiling including a comprehensive diagnostic and biomarker phenotyping.